Enhancing neuropsychological assessment clinical pathways in Parkinson's disease through the use of technology - Lobo, Elton H.; Worthy, Peter; Brooks, Deborah; Shrubsole, Kirstine; Pourzinal, Dana; Sriram, Deepa; Fels, Rachel; Yang, Ji Hyun; Liddle, Jacki; Mitchell, Leander K.; Dissanayaka, Nadeeka N. (Frontiers in Digital Health, 2025)
BackgroundRoutine administration of neuropsychological assessments to evaluate cognitive decline in Parkinson's disease (PD) may not be feasible in current clinical services. This is due to lengthy administration time, lack of specialised neuropsychologists and other limitations in resources. While technology integration could improve efficiency, understanding the existing assessment journey is crucial for successful implementation in clinical services. This preliminary study from the PDCogniCare project aims to explore current practice in neuropsychological assessments for people with PD and identify opportunities for technological integration.MethodsA qualitative study using semi-structured interviews was conducted with 15 clinical experts across two public health services in Australia. Data were analysed using inductive coding and journey mapping approaches to develop a comprehensive map of neuropsychological assessment journey.ResultsAnalysis revealed a four-phase assessment journey: initiation, brief cognitive screening, detailed neuropsychological assessment, and feedback, with distinct variations between clinical pathways. Key challenges included long waiting times, assessment duration, complex reporting, and limited awareness of cognitive assessments. While technology integration could begin to address some of these challenges through streamlined processes and improved access, barriers such as system integration, user adoption, and assessment methodology constraints require consideration.ConclusionThis study revealed the complexity of neuropsychological assessment pathways and identified potential areas for technological enhancement. Future research from the PDCogniCare project will aim to address these areas by employing appropriate methodologies and theoretical models to guide the design and development of technologies for neuropsychological assessments in PD.